Republic of Korea : Financial Sector Assessment Program-Technical Note-Systemic Risk Analysis, Financial Sector Stress Testing, and an Assessment of Demographic Shift in Korea. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
This note presents the systemic risk analysis conducted for the Republic of Korea in the course of the 2019 Korea FSAP. It comprises a forward-looking solvency analysis for banks, insurers, and pension funds, a liquidity stress test for banks, and an assessment of network and interconnectedness for a wide range of financial sector entities and their ties to the real economy. Various structural characteristics of Korea's economy and its financial system informed the features and focus for its forward-looking risk analysis. They include Korea's strong export orientation, limited diversification, and its key role as a node in regional and international supply chains. Korea's financial system has grown by 40 percentage points of GDP since 2013, enhancing the importance of a deep financial sector analysis as conducted through the FSAP. Mortgage insurance schemes are widely used-which was reflected in the way the risk assessment for banks was conducted. Korea's life and non-life insurance sector is large, highly concentrated and saturated. Fintech developments keep accelerating, in terms of its Open Banking system and e-money providers. Demographic developments in Korea are among the most adverse world-wide, implying a continuous drag on demand, downward pressure on interest rates, financial firms' income, and hence their capitalization unless they will be altering their business models.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet